THE SOCIO-PEDAGOGICAL ESSENCE OF CIVIC COMPETENCE - Baxodirovich, Djumaqulov Shuxrat (Research Focus International Scientific Journal, 2026)
This article clarifies the structure of civic competence based on the concepts of “civic competence” and “civic sense”. The key aspects and functions of civic competence are also explained.